Current Situation and Consideration about Rehabilitation of Spinal Cord Injury - Anren ZHANG (康复学报)
This article reviews the epidemiology, pathophysiology and present situation of treatment for SCI, and points out that conducting epidemiological investigation, establishing unified evaluation criterion of curative effect, arranging randomized controlled clinical trials and searching for safe and effective methods are important. The review provides some reference for the rehabilitation domain research of SCI.